C–O–H2 ternary diagram for evaluation of carbon activity in CH4-containing gas mixtures - T.R. Ribeiro; J.B. Ferreira Neto; C. Takano; J.G.R. Poço; L. Kolbeinsen; E. Ringdalen (Journal of Materials Research and Technology, 2021)
The C–O–H2 ternary diagram is presented to characterize the carbon activity in equilibrium with gas mixtures containing CH4, CO, CO2, H2O, and H2 at different temperatures and pressures. The three reactions for carbon deposition from CH4, CO, and CO + H2 are considered jointly, and the combined equilibrium carbon activity is calculated. The lines on the diagram show a set of gas compositions that is in equilibrium with a defined value of carbon activity at a given temperature and pressure. It was possible to verify that carbon activity in equilibrium with the direct reduction process gas of Midrex is 0.15 and of Energiron ZR is 8.5, explaining the higher carbon content in the reduced iron for the latter. In the case of steam reforming of methane and methanol, carbon activity in usual industrial conditions are of 0.35 and 0.73 respectively. Finally steam reforming of ethanol was evaluated and it was shown that carbon deposition is expected at 240 °C but would be avoided at temperatures of 500 °C and higher in equilibrium conditions. The proposed diagram could be useful in many chemical, catalytic, and metallurgical processes for study or prevention of carbon formation.